Estimating the Harms and Benefits of Prostate Cancer Screening As Used in Common Practice Versus Recommended Good Practice: A Microsimulation Screening Analysis - Carlsson, Sigrid V. (Cancer, 2016)
BACKGROUND: Prostate-specific antigen (PSA) screening and concomitant treatment can be implemented in several ways. We investigated how the net benefit of PSA screening varies between common practice versus “good practice.” METHODS: We used MIcrosimulation SCreening ANalysis (MISCAN) to evaluate the effect on quality-adjusted life-years (QALYs) if 4 recommendations were followed: limited screening in older men; selective biopsy in men with elevated PSA; active surveillance for low-risk tumors; and treatment preferentially delivered at high-volume centers. Outcomes were compared to a base model with annual screening starting at ages 55–69, simulated using the European Randomized Study of Screening for Prostate Cancer (ERSPC) data. RESULTS: In terms of QALYs gained compared to no screening, per 1000 screened men followed over their lifetime, recommended good practice led to 73 life-years (LYs) and 74 QALYs gained compared to 73 LYs and 56 QALYs for the base model. In contrast, common practice led to 78 LYs gained but only 19 QALYs gained; more than a 75% relative reduction in QALYs gained from unadjusted LYs gained. The poor outcomes for common practice were influenced predominantly by use of aggressive treatment for low-risk disease, with PSA testing in older men also strongly reducing potential QALY gains. CONCLUSIONS: Commonly-used PSA screening and treatment practices are associated with little net benefit. Following a few straightforward clinical recommendations, particularly greater use of active surveillance for low-risk disease and reducing screening in older men, would lead to an almost 4-fold increase in the net benefit of prostate cancer screening.